Coaching for Performance and Development Organization - Ari Apriani; Siti Annisa Wahdiniawati; Ratna Ratna; Jovi Iristian; Esti Liana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim is to discuss how Coaching for Performance and Development Organization (CPDO) works and contributes to individual coaching and development as well as organizational development. This paper uses a qualitative method by reviewing the existing literature related to Coaching for Performance and Development Organization (CPDO) and looking at the findings from research over the last 10 years related to the variables in this paper. Discussion and reinforcement of the qualitative results of this paper provide answers and contributions. Overall, the role of the CPDO in today's work environment is critical, and its ability to adapt to change and integrate sustainability principles will determine its impact in the long run. The organization must continue to evolve and provide relevant coaching and training to help individuals and organizations thrive in the ever-changing world of work.